2017
DOI: 10.1063/1.4998941
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative quantum rate model for hydrogen transfer in soybean lipoxygenase

Abstract: The hydrogen transfer reaction catalysed by soybean lipoxygenase (SLO) has been the focus of intense study following observations of a high kinetic isotope effect (KIE). Today high KIEs are generally thought to indicate departure from classical rate theory and are seen as a strong signature of tunnelling of the transferring particle, hydrogen or one of its isotopes, through the reaction energy barrier. In this paper we build a qualitative quantum rate model with few free parameters that describes the dynamics … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The pseudo-spin term of this state can be thought as the ground state of the interaction Hamiltonian H I = H (13) HB + H (24) HB with large pseudo-spin separations and vanishing hopping constants. When R 13 and R 24 become sufficiently small, a small amount of entanglement is generated through the weak X 1 −H• • • X 3 and X 2 • • • H−X 4 bonds:…”
Section: (C) Enzyme Catalysed Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pseudo-spin term of this state can be thought as the ground state of the interaction Hamiltonian H I = H (13) HB + H (24) HB with large pseudo-spin separations and vanishing hopping constants. When R 13 and R 24 become sufficiently small, a small amount of entanglement is generated through the weak X 1 −H• • • X 3 and X 2 • • • H−X 4 bonds:…”
Section: (C) Enzyme Catalysed Reactionmentioning
confidence: 99%
“…According to the kinetic isotope effects studies, observed rates of several enzyme-catalysed oxidoreduction reactions cannot be explained solely in terms of a semi-classical transition-state theory without a quantum-mechanical correction for the tunnelling of H species [8][9][10][11][12][13][14][15]. Moreover, a number of different studies, including the kinetic isotope experiments [11,12], molecular dynamic simulations [16][17][18], quantum mechanical molecular mechanics calculations [19][20][21][22][23] and qualitative quantum rate models [24] give prominence to the role of the conformational change in promoting tunnelling.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the kinetics of enzyme-substrate interactions has often assumed simple diffusion limited, or controlled, collision theory [ 71 ], the maximum value of would be around M s if every collision between the enzyme and substrate molecule results in the formation of a viable ES complex. Not surprisingly, few enzymes approach this theoretical maximum value [ 72 ], but a few do so, and some even appear to exceed it (e.g., [ 73 ]). As might be expected, cellular crowding affects diffusion rates, as well as protein aggregation and phase separation [ 74 ].…”
Section: Approximating the Activity Within The Cellmentioning
confidence: 99%
“…Unlike quantum mechanical (CRP) rates, k TST (T, η) does not account for tunneling along the reaction path. 41 To include tunneling approximately, a Wigner tunneling correction 34 κ W (T, η) = 1 + 1 24…”
Section: R and ωmentioning
confidence: 99%
“…( 9), while keeping the remaining parameters of the potential, A 2 and A 4 , constant. To account for barrier fluctuations, we use a simple stochastic averaging procedure originally suggested to model environmentinduced potential fluctuations for a hydrogen transfer reaction in a protein environment 41 .…”
Section: B Cavity-altered Thermal Quantum Isomerization Ratesmentioning
confidence: 99%